ANALISIS EFISIENSI PRODUKSI PERIKANAN DI KABUPATEN PESISIR SELATAN - Dini Asra Jaya; Alpon Satrianto (Universitas Negeri Padang, 2026)
This study examines the effects of the number of boats, fishing gear, fishermen, and fisheries entrepreneurs on fisheries production in Pesisir Selatan Regency, both partially and simultaneously. This research uses a quantitative approach with secondary panel data, combining cross-section data from 10 districts and time series data from 2013–2024. The analysis employs multiple linear regression with a panel data approach and Stochastic Frontier Analysis (SFA) to measure production efficiency. The results indicate that the number of fishing gear and fishermen has a positive and significant effect on fisheries production, while the number of boats and fisheries entrepreneurs does not have a significant effect. The efficiency level of fisheries production ranges from 0.46 to 0.49, indicating that it is still inefficient. In conclusion, optimizing the use of fishing gear and improving the capacity of fishermen are crucial to increasing production and efficiency. It is recommended that the local government strengthen guidance and empowerment programs for fishermen and enhance the effective utilization of production factors.